FAKTOR YANG MEMPENGARUHI KEJADIAN ISPA PADA BALITA - Onih Caniago; Tuti Asrianti Utami; Fulgensius Surianto (JOMIS (Journal of Midwifery Science), 2022)
ABSTRACT Acute Respiratory Infection (ARI) is a contributor to high morbidity and mortality rates in children under five every year in developing countries, including Indonesia. The cause of the incidence of ARI in toddlers is due to individual factors (age, immunization status, gender, birth weight, exclusive breastfeeding and nutritional status), physical environmental factors (type of walls, temperature, humidity and density of housing, fuel for cooking) and behavioral factors. family members who smoke in the house. The purpose of the study was to analyze the incidence of ARI in children under five at the Cinta Kasih Hospital (CK) Tzu Chi Cengkareng-West Jakarta. Descriptive quantitative research design with a cross sectional approach and using retrospective data from medical record data. The research sample was 100 children under five ARI with random sampling technique. The results of the study explained that the majority of children under five who experienced ARI had an age of <25 months as much as 55%, 52% poor nutritional status, 53% complete immunization, 47% mild ARI incidence in toddlers at Tsu Chi Hospital. Statistical analysis using the Kendall Tau-b statistical test, explained that there was a relationship between birth weight under five (p value = 0.004), nutritional status (p value = 0.000), exclusive breastfeeding (p value = 0.002) and immunization (p value = 0.024) with the incidence of ARI at Tsu Chi Hospital. The conclusion is that it is better for families, especially mothers, it is important to maintain their health during pregnancy to prevent babies from being born LBW, the correct feeding of infants and children is to give exclusive breastfeeding and then complementary foods (ASI) to make the nutritional status of toddlers good, compliance with immunizations